Pelvic Floor Muscle Training Reduces Urinary Incontinence Severity in Perimenopausal Women: A Pre-Post Intervention Study - Yulita, Defi; Intani, Trya Mia; Mehtab, Mehtab (JIK-JURNAL ILMU KESEHATAN, 2025)
Background: As one of the major factors that seriously impact perimenopausal women's quality of life, urinary incontinence is at the same time an area where evidence for a short-term intensive pelvic floor muscle training protocol is still scarce in Southeast Asian populations.Objective: The present study assessed the effectiveness of a short intensive pelvic floor muscle training of 10 days in perimenopausal women with urinary incontinence.Methods: The researchers used a one-group pretest-posttest design with 30 perimenopausal women (aged 40-49 years) suffering from urinary incontinence at Dadok Tunggul Hitam Health Center, Padang, Indonesia. The participants accomplished a 10-day intensive pelvic floor muscle training program (4-5 sessions daily, 10 repetitions per session). The International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI-SF) was used to measure incontinence severity before and after the intervention. Collected data were processed using the Wilcoxon signed-rank test.Results: The program successfully brought about a statistically significant reduction of the average ICIQ-UI-SF scores by 31.7% (4.275 to 2.921, p=0.00). As a result, the number of moderate urinary incontinence cases dropped by 38.5% (from 43.3% to 26.7%), whereas mild cases increased three times (from 6.7% to 20.0%).Conclusion: A 10-day intensive pelvic floor muscle training program is capable of dramatically reducing the severity of urinary incontinence in perimenopausal women, and hence, the intervention constitutes a potential resource-limited primary healthcare setting first-line solution.